2021
DOI: 10.1017/s0022215121000475
|View full text |Cite
|
Sign up to set email alerts
|

Arytenoid asymmetry: Is it the most predictive parameter for arytenoid adduction in unilateral vocal fold paralysis?

Abstract: Objective The aim of this study was to establish arytenoid asymmetry as a pre-operative predictive parameter for arytenoid adduction surgery in unilateral vocal fold paralysis and thereafter identify the most predictive parameter for arytenoid adduction among the established parameters. Methods A retrospective comparative study was undertaken. The ‘arytenoid asymmetry angle’ formed between skewed ‘glottic’ and ‘interarytenoid’ axes (traced along the plane of closure of the membranous and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…34 Lastly in support of the exposition that AAA is a secondary laryngeal adaptation, it has been observed in studies involving patients with unilateral vocal fold immobility with AAA, that arytenoid adduction surgery is not always required in addition to Medialization Thyroplasty in order to achieve a satisfactory voice. 35 It has also been observed that not all patients who have undergone arytenoid adduction surgery have the arytenoids restored to perfect symmetry despite a significant improvement in voice postoperatively. 36 These observations coupled with the incidental finding of arytenoid asymmetry by Lindestad et al 16 in 70% of a nondysphonic population, further endorsed our conclusion that AAA which closely parallels an abnormal muscle tension posture is secondary to a laryngeal pathology that interferes with normal phonatory function.…”
Section: Discussionmentioning
confidence: 99%
“…34 Lastly in support of the exposition that AAA is a secondary laryngeal adaptation, it has been observed in studies involving patients with unilateral vocal fold immobility with AAA, that arytenoid adduction surgery is not always required in addition to Medialization Thyroplasty in order to achieve a satisfactory voice. 35 It has also been observed that not all patients who have undergone arytenoid adduction surgery have the arytenoids restored to perfect symmetry despite a significant improvement in voice postoperatively. 36 These observations coupled with the incidental finding of arytenoid asymmetry by Lindestad et al 16 in 70% of a nondysphonic population, further endorsed our conclusion that AAA which closely parallels an abnormal muscle tension posture is secondary to a laryngeal pathology that interferes with normal phonatory function.…”
Section: Discussionmentioning
confidence: 99%
“…The goal of this surgery is to improve glottal closure by medializing the vocal folds 6,10 . This process is thought to alter quantitative measures of the vocal fold morphology including glottal gap area and vocal fold bowing 5,9,11 . Changes in these measures are frequently observed following bilateral thyroplasty, but the magnitude of these changes and how it affects voice is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The controversy of adding arytenoid procedure to ML still continues today. 8,9 This study was conducted to find a possible answer to this controversy. This study is also the first clinical study comparing ML + AA with ML + AApexy.…”
Section: Introductionmentioning
confidence: 99%